The Investigation of the Marriage and Divorce Status in Tabriz - Moradi, Mohammad (Journal of History Culture and Art Research, 2017)
This study has been carried out to investigate and analyze the secondary scale-based data and information about the marriage and divorce status in Tabriz City between 1979-1999 years. The statistical population of the present study includes four groups of married and separated people during 1979-1999. The usual family members are ranging from 15-34 years old not married people, who dwelled in Tabriz City. The present study includes 2800 samples that about 630 married, 168 divorced, and 2002 unmarried people. The results of the present study showed that Tabriz citizens pay attention to mate compatibility and the parents’ involve gets down when the couples getting older. The most important criterion of choosing a mate for Tabriz women is the family and the men try to consider the former familiarity. The educated people pay little attention to dowry in compare to illiterate people and the main reason of girls’ late marriage is subjected to the continuation of their education and boys’ economical and financial problems.